Chromosome Aberrations Produced by Mestranol in Human Lymphocyte Cultures - Teodorović Radislava (Sciendo, 2019)
In this investigation, the genotoxic properties of mestranol were examined in vitro. Human lymphocyte cultures were exposed for 72 h to mestranol at concentrations of 7.5, 15 and 30 µg/g. The genotoxic effects of the chemosterilant were assessed by numerical and structural chromosome aberrations.